The various roles of oncology nurse specialists: An international perspective - Ilana Kadmon (Elsevier, 2017)
Ilana Kadmon, PhD, RN was for many years a nurse specialist in Breast Cancer at Hadassah Medical Center, Jerusalem, Israel. From 2016, she started the role of a nurse academic consultant at the nursing division at Hadassah. Her PhD is from The University of Edinburgh, UK. Her research involved psychosocial aspects of breast cancer, and the role of the breast care nurse (BCN). She was a pioneer in developing the post of the BCN in Israel. This position was initially developed by her at Hadassah and initiated by the Israel Cancer Association. Beyond her clinical expertise, at the Hadassah School of Nursing, she lectures and writes in many areas on breast cancer care in general. She served as a board member of the European Oncology Nursing Society, and was also a member of the Editorial Committee of the European Journal of Oncology Nursing. Moreover, she serves as a reviewer for many nursing journals. She was involved in a mutual international collaborative project with nurses in Tianjin, China. She was there for seminars and initiated some cross-cultural research in the area of partners of women with breast cancer, involving both countries. Moreover, she has been invited to Cyprus, Greece Russia, and Turkey to teach and give workshops.